The prevalence of oral mucosal lesions in patients visiting a dental school in Southern India - Mathew Anuna; Pai Keerthilatha; Sholapurkar Amar; Vengal Manoj (Wolters Kluwer Medknow Publications, 2008)
The purpose of the present study was to evaluate the prevalence of oral mucosal lesions in Manipal, Karnataka State, India. A total of 1190 subjects who visited the department of oral medicine and radiology for diagnosis of various oral complaints over a period of 3 months were interviewed and clinically examined for oral mucosal lesions. The result showed the presence of one or more mucosal lesions in (41.2%) of the population. Fordyce′s condition was observed most frequently (6.55%) followed by frictional keratosis (5.79%), fissured tongue (5.71%), leukoedema (3.78%), smoker′s palate (2.77%), recurrent aphthae, oral submucous fibrosis (2.01%), oral malignancies (1.76%), leukoplakia (1.59%), median rhomboid glossitis (1.50%), candidiasis (1.3%), lichen planus (1.20%), varices (1.17%), traumatic ulcer and oral hairy leukoplakia (1.008%), denture stomatitis, geographic tongue, betel chewer′s mucosa and irritational fibroma (0.84%), herpes labialis, angular cheilitis (0.58%), and mucocele (0.16%). Mucosal lesions like tobacco-related lesions (leukoplakia, smoker′s palate, oral submucous fibrosis, and oral malignancies) were more prevalent among men than among women. Denture stomatitis, herpes labialis, and angular cheilitis occurred more frequently in the female population.